Amelioration of Coagulation Disorders and Inflammation by Hydrogen-Rich Solution Reduces Intestinal Ischemia/Reperfusion Injury in Rats through NF-κB/NLRP3 Pathway. (10th June 2020) - Yang, Ling; Guo, Yan; Fan, Xin; Chen, Ye; Yang, Bo; Liu, Ke-Xuan; Zhou, Jun
Abstract : Intestinal ischemia/reperfusion (I/R) injury often causes inflammatory responses and coagulation disorders, which is further promoting the deterioration of the disease. Hydrogen has anti-inflammatory, antioxidative, and antiapoptotic properties against various diseases. However, the effect of hydrogen on coagulation dysfunction after intestinal I/R and the underlying mechanism remains unclear. The purpose of this study was to explore whether hydrogen-rich solution (HRS) could attenuate coagulation disorders and inflammation to improve intestinal injury and poor survival following intestinal I/R. The rat model of intestinal I/R injury was established by clamping the superior mesenteric artery for 90 min and reperfusion for 2 h. HRS (10 or 20 mL/kg) or 20 mL/kg 0.9% normal saline was intravenously injected at 10 min before reperfusion, respectively. The samples were harvested at 2 h after reperfusion for further analyses. Moreover, the survival rate was observed for 24 h. The results showed that HRS improved the survival rate and alleviated serum diamine oxidase activities, intestinal injury, edema, and apoptosis. Interestingly, HRS markedly improved intestinal I/R-mediated coagulation disorders as evidenced by abnormal conventional indicators of coagulation and thromboelastography. Additionally, HRS attenuated inflammatory responses and the elevated tissue factor (TF) and inhibited nuclear factor kappa beta (NF- κ B) and nucleotide binding and oligomerization domain-like receptor family pyrin domain-containing 3 (NLRP3) inflammasome activation in peripheral blood mononuclear cells. Moreover, inflammatory factors and myeloperoxidase were closely associated with TF level. This study thus emphasized upon the amelioration of coagulation disorders and inflammation by HRS as a mechanism to improve intestinal I/R-induced intestinal injury and poor survival, which might be partially related to inhibition of NF- κ B/NLRP3 pathway.